“K-Pop is Part of who I am”: Cultural Discourse in Politeness Strategies and Appraisal Expressions of Indonesian K-Pop Fandom - Maisaroh, Ajeng Dilla (Universitas Negeri Medan, 2024)
This study investigates how Indonesian K-pop fans interact in online discourse utilising politeness techniques and assessment expressions. Data were obtained using a qualitative approach with virtual ethnography, including questionnaires, social media observations, and textual analysis. Politeness Theory (Brown & Levinson, 1987) examines how fans preserve group cohesion and resolve problems, whereas Appraisal Theory (Martin & White, 2005) investigates how emotions, judgements, and evaluations influence fan interactions. The data show that supporters utilise positive politeness to foster unity, negative politeness to diffuse disagreements, and direct or indirect expressions in intense debates. Meanwhile, appraisal analysis reveals that fandom discourse incorporates emotional responses, idol evaluations, and aesthetic enjoyment. These findings demonstrate how K-pop fandom operates as a dynamic linguistic arena, with politeness and assessment tactics influencing digital discourse and cultural identity construction.